The Implementation of Tax Management in The Effort Tax Efficiency - Linawati, Linawati (EAJ (Economic and Accounting Journal), 2022)
This research aims to apply tax management for tax efficiency and reliable tax data. In this research, the method used is Applied Research. The data collection techniques used are interviews and documentation. The results of this study show that PT X is a taxpayer who complies with taxation; this can be seen from tax administration or compliance tax, where tax payments and reporting are made before maturity. The company has complete accounting records, audited financial statements, and proof of transactions that are neatly arranged and sequentially numbered. The tax management strategies applied are making tax equalization working papers in the Periodic Tax Return VAT with the Corporate Income Tax Return, making working papers reconciling income tax withholding and collection with the Corporate Income Tax Return, improving accounting records separated between service costs and material costs to avoid the imposition of higher taxes, changing the PPh 21 tax burden borne to be supported and avoiding expenses that cannot be deducted according to tax regulations. From this application, PT X can avoid administrative sanctions and save taxes. This research is a development of previous research on tax management applied in the form of administration and compliance, tax planning, tax control, and Other Tax Matters.